2020
DOI: 10.1097/mpg.0000000000002759
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Inflammation Alters the Expression of Hepatic Bile Acid Receptors Causing Liver Impairment

Abstract: The gut-liver axis has been recently investigated in depth in relation to intestinal and hepatic diseases. Key actors are bile acid (BA) receptors, as farnesoid-X-receptor (FXR), pregnane-X-receptor (PXR) and G-protein-coupled-receptor (TGR5), that control a broad range of metabolic processes as well as inflammation and fibrosis.The present study aims to investigate the impact of intestinal inflammation on liver health with a focus on FXR, PXR and TGR5 expression. The strategy to improve liver health by reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…A similar decrease was also seen in FGF19 expression in adult patients with CD [57,63]. Interestingly, children with either UC or CD have significantly decreased expression of FXR in areas of active disease [64], which may explain why childhood IBD responds differently than in adults.…”
Section: Discussionmentioning
confidence: 63%
“…A similar decrease was also seen in FGF19 expression in adult patients with CD [57,63]. Interestingly, children with either UC or CD have significantly decreased expression of FXR in areas of active disease [64], which may explain why childhood IBD responds differently than in adults.…”
Section: Discussionmentioning
confidence: 63%
“…It was also revealed that the bile acid-activated receptor PXR modulated the communications between the intestinal immune system and intestinal microbiota (87). Moreover, additional studies reported the increased infiltration of inflammatory cells accompanied with the decreased expression of PXR in the liver of colitis mice treated with DSS (88). Collectively, these studies provided a preliminary hint that PXR may serve as a mediator in the "gut-liver" axis.…”
Section: Othersmentioning
confidence: 89%
“…Metabolites enriched in the bile pathway were associated with regulating carbohydrate and lipid absorption and energy metabolism [ 49 ]. Bile acids (BA) could promote the absorption of vitamins in the intestine and improve the immune function of the body to maintain individual health [ 50 , 51 ]. Lithocholic acid and deoxycholic acid could regulate bile levels and hepatoenteric circulation by activating the Farnesoid X receptor (FXR).…”
Section: Discussionmentioning
confidence: 99%